RFWD3 Participates in the Occurrence and Development of Colorectal Cancer via E2F1 Transcriptional Regulation of BIRC5 - Xu, Fenghua; Xiao, Zhifeng; Fan, Liqin; Ruan, Guangcong; Cheng, Yi; Tian, Yuting; Chen, Minjia; Chen, Dongfeng; Wei, Yanling (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Colorectal cancer (CRC) is one of the most common human malignancies. It was reported that the alterations in the DNA damage response (DDR) pathways are emerging as novel targets for treatment across different cancer types including CRC. RFWD3 plays a critical role in replication protein A (RPA)-mediated DNA damage in cancer cells. More importantly, RFWD3 can response to DNA damage by positively regulating p53 stability when the G1 cell cycle checkpoint is activated. However, the functional significance of RFWD3 in CRC has not been reported in the existing documents. Materials and Methods: Here, we revealed high expression of RFWD3 in CRC tissues by IHC analysis and The Cancer Genome Atlas (TCGA) database. Besides, overexpression of RFWD3 in CRC cell lines was also confirmed by qRT-PCR and western blot assay. The Celigo cell counting method and wound-healing/transwell migration assay were applied to evaluate CRC cell proliferation and migration. The tumor growth indicators were quantified in nude mice xenografted with shRFWD3 and shCtrl RKO cells. Results: The results indicated that RFWD3 knockdown restricted CRC development in vitro and in vivo. In exploring the downstream mechanism of RFWD3’s action, we found that RFWD3 could transcriptionally activate BIRC5 by interacting with E2F transcription factor 1 (E2F1). Accordingly, we identified BIRC5 as a downstream gene of RFWD3 regulating CRC. Subsequent loss- and gain- of function experiments demonstrated that upon overexpressing BIRC5 in RKO cells with down-regulated RFWD3, the inhibitory effects of cell proliferation, migration and colony formation could be reversed, while the capacity of cell apoptosis was ameliorated, suggesting that the effects of RFWD3 depletion was mainly due to BIRC5 suppression. Conclusions: Taken together, this study revealed that RFWD3 participates in the occurrence and development of colorectal cancer via E2F1 transcriptional regulation of BIRC5.